Relative performance of yellow sarson (Brassica rapa var glauca) and toria (B. rapa var napus) grown at different, salinity levels with different chloride and sulphate ratios - SHARMA, S K; MANCHANDA, H R (The Indian Journal of Agricultural Sciences, 2013)
A greenhouse study was conducted on a sandy soil (Typic Torripsamments) with 'RH 30' yellow sarson or raya[Brassica rapa (L.) Thell. emend. Metzger var glauca (Roxb.) Schulz] and 'Sangam' toria [B. rapa (L.) Thell. emend.Metzger var napus L.]. The crops Were grown from seeding to maturity at 5 salinity levels (ECe 4, 6, 8, 9.5 and 11.5 dS/m), each with 5 C1- : So42- ratios (9 : 1,7 : 3, 5 : 5,3.: 7 and 1 : 9) along with a non-saline (ECe 1.3 dS/m) control.Germination of both the crops was neither delayed nor affected at ECe 4 dS/m. Germination in raya and toria at ECe 6, 8,9.5 and 11.5 dS/m and different C1-: SO42- ratios, however, decreased by 12 and 5, 50 and 18,50 and 25, 58 and 34% respectively. Germination of raya was delayed by 3 days at ECe 8 and by 6 days at ECe 9.5 and 11.5 dS/m compared with that by 3, 6 and 9 days in toria at the respective Eee levels. On an average, raya gave significantly more (24%) seed yield up to ECe 6 dS/m. There was also no significant reduction in the seed yield of raya and toria up to 'ECe 8 dS/m. However, at ECe 9.5 and 11.5 dS/m the seed yield of raya decreased by 19 and 26% compared with a reduction of 29 and 40% in toria, indicating that the former was more tolerant to salinity than the latter. The oil content in raya decreased significantly even at ECe 8.0 dS/m but only at the highest (9 : 1) C1 : SO4 ratio in the soil, whereas it was not affected ,significantly even at ECe 9.5 and 11.5 dS/m at lower C1 : SO4 ratios.